Improvement on Determination Method Esterification-Rate During Chloroacetate Esters Production Process - Xue, Jianwei; Qi, Beibei; Wen, Xiaoguang; Chai, Jingping; Lv, Zhiping; Li, Fuxiang (Asian Journal of Chemistry, 2012)
The result of esterification reaction, as the middle control, plays a key role in production of chloroacetate esters. Usually the esterification of sample was calculated by its acid values and the sample is titrated by the standard solution of potassium hydroxide ethanol before and after the reaction. We proposed to use the standard solution of sodium methoxide ethanol to substitute for the conventional potassium hydroxide ethanol standard solution. By analyzing the ester rate of isopropyl chloroacetate and isooctyl chloroacetate reaction solutions, we found the ester hydrolysis effectively suppressed in our new method. Chromogenic time was changed from original 5-8s to 1-2.3 min, thus the endpoints could be more easily identified. By the test of verification of the mixture of chloroacetic acid and chloroacetate esters, test results were more accurate in analysis.